ANALYSIS OF THE INFLUENCE LEARNING MODEL ON MATHEMATICS PROBLEM SOLVING ABILITIES TO CLASS VIII STUDENT AT MTSN MODEL MAKASSAR - Yulianti, Yulianti (Universitas Negeri Makassar, 2018)
The research aims to describe the influence of MMP learning model with problem solving approach on mathematics problem solving approach on mathematics problem solving abilities to class VIII students at MTsN Model Makassar. The research is eksperimen research. The populations of the research were all of students in class VIII.4 as experiment class and class VIII.6 as control class chosen by using simple random sampling technique. The data were collected by using instrument namely learning implementasion observation sheet, student’ activities observation sheet, and problem solving ability test. The data were analyzed by using descriptive and inferential analysis. The result of the research reveal that the students’ activities in experiment class in learning are in learning are in active category with the mean score 3.53 while the students’ activities in control class in learning are inactive category with the mean score 2.53. Mathematics problem solving deviation standard 9.01, and classical completnes level 92%, while Mathematics problem solving abilities of students in control class are in high category with the mean 72.65, and deviation standard 5.55, and classical completeness level 53%. In general, it can be concluded that Missoury Mathematics Project learning model has positive influence on Mathematics problem solving abilities of class VIII at MTsN Model Makassar